(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
Among the Sustainable Development Goals in the 2016-2030 Agenda, 4 is aimed at achieving inclusive, quality education for all, promoting a culture of peace. In the teaching of a foreing language, intercultural communication is essential. However, in times when confinement and non-attendance spoil an interaction between natives and non-natives that fosters adequate intercultural communication, the Faculty of Spanish for Non Speakers Spanish of Havana University has been forced to find the ideal ways to meet the objectives proposed in the career curriculum. One of them has been the University Extension. The objective of this work is to expose the experiences of the Faculty to develop the communication skills of the learners and their insertion in the community from the University Extension and the achievements in times of COVID-19.